Molecular characterization of antimicrobial resistance genes against Staphylococcus aureus isolates from Trinidad and Tobago - Patrick E. Akpaka (Journal of Infection and Public Health, 2017)
Summary: Staphylococcus aureus continues to pose major public health challenges in many areas because of antibiotic resistance problems. In the Caribbean, especially Trinidad and Tobago, the challenge is not different. This study was performed to evaluate the antimicrobial resistance gene prevalence among S. aureus isolates in Trinidad and Tobago.Standard and molecular microbiological methods, including the Microscan automated system, DNA microarray and multi locus sequence typing (MLST) analysis, were performed on 309 clinical S. aureus isolates recovered from patients who were treated at three of the country's main health institutions.S. aureus exhibited susceptibilities ≥80% to eleven of the 19 antimicrobials tested against it, and these belong to the most commonly used and available antibiotics in the country. While the antibiotic to which it was most susceptible of the commonly used antibiotics was trimethoprim/sulfamethoxazole, the antibiotics to which it was least susceptible or most resistant to were ampicillin and penicillin. S. aureus isolates from the pediatric ward produced the greatest rate of susceptibility among the isolates recovered from patients admitted into hospitals, while isolates from Accident and Emergency rooms displayed the greatest susceptibilities among patients from the community.S. aureus isolates from the country did not harbor acquired resistant genes targeting clindamycin/macrolides (ermB), linezolid (cfr) or vancomycin (vanA). The blaZ gene, which is the most common beta lactam (Penicillinase) resistance mechanism for S. aureus, was observed in 88.7% of the methicillin susceptible S. aureus, while methicillin resistance mediated by the mec gene was present in 13.6%. Most of the resistance markers found in MRSA isolates were significantly associated with the ST239-MRSA-III strain in this study, and all isolates that belonged to the USA300 strain, which additionally encoded both the PVL gene and ACME cluster, belonged to CC8.Several resistant genes, such as vanA, cfr and ermB, mediating resistance in S. aureus, are currently non-existent in Trinidad and Tobago. However, the majority of SCCmec genes were observed, suggesting that there is ongoing nosocomial transmission with minimal community transmission. This calls for stringent antibiotic stewardship and policies in the country. Keywords: Staphylococcus aureus, MSSA, MRSA, Trinidad and Tobago, Clonal complexes, MLST, PVL, ST239-MRSA III, ST8-MRSA IV, USA300